Histopathological subgroups in knee osteoarthritis. Issue 1 (January 2017) - Wyatt, L.A.; Moreton, B.J.; Mapp, P.I.; Wilson, D.; Hill, R.; Ferguson, E.; Scammell, B.E.; Walsh, D.A.
Summary: Objective: Osteoarthritis (OA) is a heterogeneous, multi-tissue disease. We hypothesised that different histopathological features characterise different stages during knee OA progression, and that discrete subgroups can be defined based on validated measures of OA histopathological features. Design: Medial tibial plateaux and synovium were from 343 post-mortem (PM) and 143 OA arthroplasty donations. A 'chondropathy/osteophyte' group ( n = 217) was classified as PM cases with osteophytes or macroscopic medial tibiofemoral chondropathy lesions ≥grade 3 to represent pre-surgical (early) OA. 'Non-arthritic' controls ( n = 48) were identified from the remaining PM cases. Mankin histopathological scores were subjected to Rasch analysis and supplemented with histopathological scores for subchondral bone marrow replacement and synovitis. Item weightings were derived by principle components analysis (PCA). Histopathological subgroups were sought using latent class analysis (LCA). Results: Chondropathy, synovitis and osteochondral pathology were each associated with OA at arthroplasty, but each was also identified in some 'non-arthritic' controls. Tidemark breaching in the chondropathy/osteophyte group was greater than in non-arthritic controls. Three histopathological subgroups were identified, characterised as 'mild OA', or 'severe OA' with mild or moderate/severe synovitis. Conclusions: Presence and severity of synovitis helps define distinct histopathological OA subgroups. The absence of a discrete 'normal' subgroup indicates a pathological continuum between normality and OA status. Identifying specific pathological processes and their clinical correlates in OA subgroups has potential to accelerate the development of more effective therapies.